Simulation of soil organic carbon potential sequestration for high Andes Peruvian croplands - Carbajal Llosa, Carlos Miguel (2025)
Soil organic carbon (SOC) sequestration in croplands represents a significant opportunity to mitigate climate change by removing carbon dioxide from the atmosphere. Simulation tools are increasingly used to assess the impact of climate change and soil management on soil organic carbon stock dynamics. Although Andean soils typically store large amounts of organic carbon, agricultural practices, especially plowing, may deplete these stocks, creating a need to understand these dynamics better. Here, we show the soil organic carbon sequestration potential in croplands in the Peruvian Andean region over 50 years. Soil organic carbon content and bulk density were spatially predicted across the study area using 100 georeferenced soil samples to quantify organic carbon stocks. Spatial interpolation was performed using Ordinary Kriging with exponential and spherical variogram models, which provided the best fit to the data. The RothC model was used to simulate changes in soil organic carbon stocks under two contrasting agricultural management scenarios: one without manure application and another with annual application of one ton of manure per hectare. We found that manure application can substantially increase soil organic carbon sequestration in croplands with increases ranging from 105.22 to 214.94 Mg ha-¹ over 50 years. The potential for increased carbon sequestration through manure application could help compensate for losses in other areas of the watershed, particularly grasslands (74.4 % of the area). This study contributes valuable information for developing sustainable land management strategies in Andean agroecosystems.